Knowledge and Attitude of Using Anabolic Androgenic Steroids Among Male Bodybuilders in Al-Russafa Baghdad Province - Sura Mohammed Challab; anwer, zina mudhafar; khalil, heba hashim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Anabolic androgenic steroids are being more popular between bodybuilders and people who are using gym to enhance their physiques. However, according to the increase of the laws prohibiting sales of these substances without physician prescription, the route of getting and administration practices have become more and more dangerous. Anabolic androgenic steroids include many synthetic derivatives of testosterone its play a significant role in medical treatment. These groups of medications are extensively abused at young ages to rising lean body mass and advance the athletic quality of performance. It has been described that anabolic steroids use can cause many long and short-term side effects, this study intended to assess the level of knowledge about AAS and its effects among gym users. 50 bodybuilders were using gym routinely and were using AASs for at least 2 months and another who were using gym routinely but never use AAS before were interviewed to show their knowledge about short and long term AASs using side effects. Participants used androgenic hormones for three main reasons health, social and personal, vast majority of the participants obtained the required results by using AAS, The majority of participants were going into the gym five to six times weekly for an hour daily. Enanthate was the main steroid abused by the participants and the gym coaches were the major source of selling steroids to the participants. The anabolic androgenic steroids had a harmful effect and abused by large number of young ages.